Peran Audit Internal Dalam Mencegah Kecurangan (Fraud) pada Organisasi Pemerintah Daerah - Antonia Zakaria Seran; Anjela Casandra Minggus; Eufracia Placida Manek; Mariana Ratu Rosario Meni; Stefen Ardi Melkisedek Ton; Susana Purnamasari Baso (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Local governments have a major responsibility in managing public finances and ensuring accountable public services. Nevertheless, cases of fraud such as budget misuse, financial report manipulation, and irregularities in procurement processes are still frequently identified. These conditions indicate weaknesses in internal control mechanisms and highlight the importance of internal audit functions. This study aims to examine the role of internal audit in preventing fraud within local government organizations in Indonesia. The research employs a library research method by reviewing relevant books, regulations, and recent scientific journals related to internal audit, fraud prevention, and public sector governance. The findings indicate that internal audit plays a strategic role in fraud prevention through three main mechanisms: fostering an organizational culture that emphasizes integrity and ethical values, implementing and evaluating anti-fraud control systems, and developing continuous and independent oversight processes. In addition, the effectiveness of internal audit is supported by proper audit planning, comprehensive field audit implementation, and consistent follow-up of audit findings. However, the study also reveals that the optimal role of internal audit is constrained by limited human resources, budgetary restrictions, and insufficient support from organizational leadership. Strengthening institutional commitment and auditor capacity is therefore essential to enhance fraud prevention in local government.